2000
DOI: 10.1161/01.res.87.5.e1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Angiotensin-Converting Enzyme–Related Carboxypeptidase (ACE2) Converts Angiotensin I to Angiotensin 1-9

Abstract: ACE2, the first known human homologue of angiotensin-converting enzyme (ACE), was identified from 5' sequencing of a human heart failure ventricle cDNA library. ACE2 has an apparent signal peptide, a single metalloprotease active site, and a transmembrane domain. The metalloprotease catalytic domains of ACE2 and ACE are 42% identical, and comparison of the genomic structures indicates that the two genes arose through duplication. In contrast to the more ubiquitous ACE, ACE2 transcripts are found only in heart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
3,142
4
94

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,832 publications
(3,279 citation statements)
references
References 21 publications
39
3,142
4
94
Order By: Relevance
“…For example, a new gene in the ACE family, the ACE2 gene, has been identified and shown to map to defined quantitative trait loci on the X chromosome [3,4]. Although there is significant homology in their respective protein sequences, ACE and ACE2 appear to have opposing roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a new gene in the ACE family, the ACE2 gene, has been identified and shown to map to defined quantitative trait loci on the X chromosome [3,4]. Although there is significant homology in their respective protein sequences, ACE and ACE2 appear to have opposing roles.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be genetic differences between men and women with CHF. In particular, a new gene in the angiotensin converting enzyme (ACE) family, the ACE2 gene, has been identified and shown to map to defined quantitative trait loci on the X chromosome [3,4]. However, little is known about whether there are differences in the optimal treatment of CHF between men and women.…”
Section: Introductionmentioning
confidence: 99%
“…128 In the kidney, ACE2 has a distribution similar to ACE, with major localization in renal tubules. [128][129][130] It has been suggested that both mRNA and protein expression of ACE2 are reduced in kidney biopsy specimens from type 2 diabetic patients with nephropathy compared with normal controls or patients with other renal disease. 131 In another study, ACE2 levels in kidney biopsy of diabetic patients were reduced only at the protein level, not at the mRNA level, and only in the tubulointerstitial region, not in the glomeruli, compared with non-diabetic controls.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…The presence of a significant interaction term (HR 0.89, CI 0.83-0.95) in our study suggests that ACE inhibitors may act differently in women and men with CHF. Recently, a new gene in the ACE family, the ACE2 gene, has been identified and shown to map to defined quantitative trait loci on the X chromosome [25,26]. ACE and ACE2 appear to have opposing roles.…”
Section: Discussionmentioning
confidence: 99%